2014
DOI: 10.7567/jjap.53.121201
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in interface state density of SiO2/Si-IPL/InP by fluorine and sulfur passivations

Abstract: The characteristics of a liquid-phase-deposited SiO 2 film on InP were investigated. The mixture of H 2 SiF 6 and H 3 BO 3 aqueous precursors was used as the growth solution. SiO 2 on InP with (NH 4 ) 2 S treatment showed good electrical characteristics owing to the reduction of native oxides and sulfur passivation. The electrical characteristics were further improved with an ultrathin Si interface passivation layer (IPL) through reductions in Fermi-level pinning and interface state density. Moreover, during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was also found that the Poole-Frenkel emission dominates the reverse current in both diodes, indicating the presence of structural defects and trap levels in the dielectric film. The density of states values for Au/BST/n-InP with Rs was found to be 2.97×10 11 eV -1 cm -2 , which is of the same order as in [44].…”
Section: = -mentioning
confidence: 54%
“…It was also found that the Poole-Frenkel emission dominates the reverse current in both diodes, indicating the presence of structural defects and trap levels in the dielectric film. The density of states values for Au/BST/n-InP with Rs was found to be 2.97×10 11 eV -1 cm -2 , which is of the same order as in [44].…”
Section: = -mentioning
confidence: 54%